REPOSISI POLITIK HUKUM PERJANJIAN INTERNASIONAL DALAM RANGKA MEWUJUDKAN TERTIB HUKUM DI INDONESIA - Dhiana Puspitawati; Adi Kusumaningrum (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2015)
In Indonesia, here is no exact politic and legal system regarding the application of International Treaty within national legal system. Article 11 of Indonesian Constitution 1945 merely envisages the division of authority between President and Parliament in ratifying international treaty, however, such article does not state clearly Indonesia’s legal politics concerning the application of international treaty within national legal system. The lack of clarification on Indonesia’s legal and political system in such area raises problems in the application of international treaty domestically. This research is aimed to: (1) analyses Indonesia’s legal politic concerning the application of international treaty towards Indonesian Constitution 1945 as well as other legal instruments; (2) analyses legal implications of international treaty upon Indonesia’s national interests and; (3) propose concept on legal politic regarding the application of international treaty in Indonesia. Since legal politic is crucial in supporting which law should be implemented towards state’s national goal, it is important to clarify Indonesia’s legal politic concerning the implementation of international treaty. As stated by Hans Kelsen, that as the application of the rule of law, a state should eliminate existing inconsistency and overlaps of its laws.